ONLINE EDUCATION: OPPORTUNITIES AND CHALLENGES IN THE DIGITAL AGE - Yergeshova Nafisa Shuxrat qizi (PEDAGOGS, 2025)
Abstract: Online education has become a significant part of the global education system, especially after the COVID-19 pandemic accelerated its growth. This paper explores the advantages and limitations of online learning, focusing on accessibility, flexibility, cost-efficiency, and technological barriers. It examines how digital learning tools have changed the traditional classroom environment and discusses the role of teachers and institutions in maintaining quality. The paper concludes that while online education offers numerous benefits, careful planning and equal access are necessary to ensure its effectiveness and inclusivity.